Relationship between organization antecedent, job satisfaction and knowledge sharing practices among academician at Malaysia research universities. - Abdullah, Nurfarahin Jasmine See; Ismail, Ismi Arif; Idrus, Khairuddin; Steven, Eric Krauss (Universiti Sains Malaysia, 2014)
The purpose of this research is to find out the relationship between organization antecedent, job satisfaction and knowledge sharing practices among academician at Malaysia Research Universities. The theory of this research are organization antecedent has a relationship with job satisfaction and knowledge sharing practice and job satisfaction has relationship with knowledge sharing practices and this is single mediation. The variables in this research for organizational antecedent consist of people, organization, and technology while else job satisfaction consists of job, salary, promotion, supervisor and co-worker, as for knowledge sharing practice consist of socialization, externalization, combination and internalization.